ECONOMIC IMPACTS OF THE EU'S ANTI DEFORESTATION LAW ON INDONESIA: ECONOMIC IMPACTS OF THE EU'S ANTI DEFORESTATION LAW ON INDONESIA - Hurin in lia; Dilla Cattleyana (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
The EU is Indonesia's third largest trading partner after the Southeast Asia region (ASEAN) and the People's Republic of China. Even in the conditions of the Covid-19 pandemic, the value of Indonesia's exports to the European Union increased by 26 percent in 2021 to 16.5 billion euros. This growth was partly influenced by rising prices of raw materials such as palm oil. Exports of palm oil to EU countries increased by 9 percent. On 28 June 2022, the Council of the European Union issued a press release on Council approval of new regulations to reduce deforestation and forest degradation worldwide. The Council of the European Union has announced that it will finalize its negotiating position (general approach) on a proposal to limit the consumption of products that affect deforestation or forest degradation. This research is a literature review and the result of researchers' thingking. The type of data used is secondary data with a qualitative approach. EU deforestation laws could cost the Indonesian government $5.15 billion in lost revenue